2003
DOI: 10.1161/01.cir.0000050621.67499.7d
|View full text |Cite
|
Sign up to set email alerts
|

Role of Risk Factors in the Modulation of Tissue Factor Activity and Blood Thrombogenicity

Abstract: Background-Several studies suggest a role for an increased circulating pool of tissue factor (TF) in atherothrombotic diseases. Furthermore, certain cardiovascular risk factors, such as diabetes, hyperlipemia, and smoking, are associated with a higher incidence of thrombotic complications. We hypothesized that the observed increased blood thrombogenicity (BT) observed in patients with type 2 diabetes mellitus may be mediated via an increased circulating tissue factor activity. We have extended our study to smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
189
2
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(208 citation statements)
references
References 40 publications
7
189
2
10
Order By: Relevance
“…After “validating” our model, we first sought to investigate the impact of e‐cigarettes on thrombogenesis, as it is the major cause of tobacco‐induced CVD,38 including thrombosis‐based diseases 17, 77, 78, 79, 80, 81, 82, 83. Our findings revealed, for the first time, a drastic reduction in the time for carotid artery occlusion, indicating a prothrombotic phenotype, even after only a week of whole‐body exposure to e‐cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…After “validating” our model, we first sought to investigate the impact of e‐cigarettes on thrombogenesis, as it is the major cause of tobacco‐induced CVD,38 including thrombosis‐based diseases 17, 77, 78, 79, 80, 81, 82, 83. Our findings revealed, for the first time, a drastic reduction in the time for carotid artery occlusion, indicating a prothrombotic phenotype, even after only a week of whole‐body exposure to e‐cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesized mechanism for superior response of smokers to thrombolytic therapy is that smoking does not affect atherosclerotic plaque vulnerability as much as it increases hypercoagulability. Smoking has been directly associated with a procoagulant state with effects on endothelial dysfunction, increased platelet activation and aggregation, increased circulating levels of fibrinogen, and increased thrombin generation 36, 37. Components of cigarette smoke have also been shown to impair fibrin crosslinking 38.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier concept that blood coagulation is initiated after vascular damage when blood is exposed to "extrinsic" tissue factor has been broadened by the observations that tissue factor is also present in circulating blood (13,14,16,17) and that hematopoietic cell-associated tissue factor is important in thrombogenesis (18). For instance, circulating tissue factor has been associated with increased blood thrombogenicity in patients with cardiovascular disease (30), sickle cell disease (17), antiphospholipid antibody syndrome (31), hyperlipidemia (20), and disseminated intravascular coagulation (32). In addition, we (19) and others (20) have reported that patients with type 2 diabetes have increased blood levels of tissue factor PCA.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue factor, which is present in the adventitia of normal blood vessels and is highly expressed in atherosclerotic plaques, has been recognized to initiate coagulation and thrombus formation when the vessel wall is injured or plaques are fissured (15). More recently, it has been shown that there is, in addition, a circulating pool of tissue factor in blood that is associated with cells and microparticles, is thrombogenic (13,14,16 -18), and is elevated in type 2 diabetes (19,20). Because premature ASVD risk depends partially on glycemic control (21,22), we hypothesized that hyperglycemia and/or hyperinsulinemia contribute to the rise in circulating tissue factor and to the prothrombotic state in these patients.…”
mentioning
confidence: 99%